EFFECT OF NANO FERTILIZER ON GROWTH, YIELD, NITROGEN UPTAKE AND ECONOMICS OF RICE IN ALLUVIAL SOILS OF GODAVARI ZONE OF ANDHRA PRADESH - P V , RAMESH BABU (The Journal of Research ANGRAU, 2026)
A field trial was conducted during the Kharif and Rabi seasons of 2023–24 to evaluate theefficacy of nano urea (NU) and super nano urea (SNU) on the growth, yield, nutrient uptake, andeconomics of rice. The experiment consisted of 11 treatments: T1–Control (0% N; 100% P & K);T2–Recommended Fertilizer Dose (RDF) representing 100% RDN (Kharif: 90-60-60 kg NPK ha-1;Rabi: 180-90-60 kg NPK ha-1); T3–50% RDN; T4- 50% RDN + two sprays of conventional urea@1.0% at active tillering (AT) and panicle initiation (PI) stages; T5- 50% RDN + two  sprays of NU@0.4% at A.T & PI; T6- 50% RDN + three sprays of NU @0.4% at A.T, PI & heading; T7- 50% RDN+ two sprays of SNU @0.25% at A.T & PI; T8- 50% RDN + two sprays of SNU @0.5% at A.T & PI;T9- 50% RDN + two sprays of SNU @1.0% at A.T & PI; T10- 33% RDN + three sprays of SNU@0.5% at A.T, PI & heading; and T11- 66% RDN + one spray of SNU @0.5% at heading. Theresultsrevealed that the application of 50% RDN with two foliar sprays of nano urea at the activetillering and panicle initiation stages (T8) proved effective in enhancing rice growth, yield attributes,grain and straw yields, economic returns and nitrogen uptake. However, this treatment performedon par to the 100% RDN (T2) across two consecutive seasons on alluvial soils of the Godavarizone.